2006
DOI: 10.1016/j.febslet.2006.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Binding of antibiotic amphotericin B to lipid membranes: A 1H NMR study

Abstract: The 1 H NMR technique was applied to study binding of AmB, an antifungal drug, to lipid membranes formed with egg yolk phosphatidylcholine. The analysis of 1 H NMR spectra of liposomes, containing also cholesterol and ergosterol (at 40 mol%), shows that AmB binds preferentially to the polar headgroups. Such a binding restricts molecular motion of the choline fragment in the hydrophilic region at the surface of liposomes but increases the segmental motional freedom in the hydrophobic core. The same effects are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
61
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 35 publications
4
61
0
Order By: Relevance
“…It has been also proposed that selectivity toward cells of fungi is based upon a difference of the radii of porous structures of AmB binding ergosterol and cholesterol [6,9]. On the other hand, very recent reports show that alternatively both the biological action of the drug as well as toxic side effects may be directly related to the effect of AmB on physical properties of the membranes [10][11][12][13]. The 1 H-NMR technique studies demonstrated that the polar headgroup region of the membranes, rather than the hydrophobic core, is a predominant site of binding of AmB from the water phase [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been also proposed that selectivity toward cells of fungi is based upon a difference of the radii of porous structures of AmB binding ergosterol and cholesterol [6,9]. On the other hand, very recent reports show that alternatively both the biological action of the drug as well as toxic side effects may be directly related to the effect of AmB on physical properties of the membranes [10][11][12][13]. The 1 H-NMR technique studies demonstrated that the polar headgroup region of the membranes, rather than the hydrophobic core, is a predominant site of binding of AmB from the water phase [12].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, very recent reports show that alternatively both the biological action of the drug as well as toxic side effects may be directly related to the effect of AmB on physical properties of the membranes [10][11][12][13]. The 1 H-NMR technique studies demonstrated that the polar headgroup region of the membranes, rather than the hydrophobic core, is a predominant site of binding of AmB from the water phase [12]. Analysis of the effect of AmB on structural and dynamic properties of lipid membranes carried out with application of SANS (small angle neutron scattering), 1 H-NMR and FTIR techniques showed that AmB molecules, even bound to the lipid polar groups, influence motional freedom of acyl lipid chains [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter case, AmB is postulated to self-aggregate into the hydrophilic pores that may severely affect transmembrane ion transport [8][9][10]. On the other hand, the results of the recent structural studies show that the pharmacological effect of AmB towards the membranes may be associated with modification of structural and dynamic properties of the lipid bilayer [11][12][13][14]. Despite the exact mode of action of AmB it is without doubt that both the pharmacological activity and the toxic side effects are strongly dependent on molecular organization of the drug in formulation [1,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The ability of AmB to form ring-shaped molecular aggregates has been demonstrated by the scanning force microscopic analysis of monomolecular layers of the drug [10]. On the other hand, the results of recent experiments carried out with application of the 1 H-NMR [11] and FTIR [12] techniques demonstrated that the principal site of localization of AmB with respect to the lipid membrane is the polar headgroup region. The results of the linear dichroism analysis of orientation of AmB molecules in the lipid membranes were interpreted in terms of existence of two pools of AmB, one parallel and one perpendicular with respect to the plane of the lipid bilayer [13,14].…”
Section: Introductionmentioning
confidence: 99%